The Effect of Turmeric Drink on Rat Cholesterol Level - Nino Yayah Sadiyyah; Ahmad Sulaeman; Edi S Mudjajanto (Media Gizi dan Keluarga, 2000)
The objective of this study is to learn the effect of turmeric drink on total cholesterol, HDL and LDL levels of rats. There are tree kinds of turmeric drink, which were given to experimental rats: 1) traditionaly turmeric drink; 2) spray drier turmeric drink and 3) extract turmeric drink. The study showed that all kinds of turmeric drink decreased cholesterol. Traditionally turmeric drink decreased total cholesterol and LDL higher than others and spray drier turmeric drink could maintain HDL.